Exploring Policy Options for a New Rural America: Conference Synthesis - Johnson, S. R. (Acta Agraria Debreceniensis, 2002)
This Conference has more then lived up to its billing, exploring policy options for a new rural America but in addition identifying the basis for a new framework for rural policy. Evidence that a new policy framework is needed is abundant (Stauber). In one way or another, rural areas of North America and of most of the developed world have for at least the past century experienced secular decline compared to urban areas. This has occurred during a period of high government transfers or subsidies, both direct and from policy interventions that have distorted the functioning of markets. It is clear that the systemic discrepancy between rural and urban populations/areas is a public policy priority. It is just as clear that there has not been a consensus on how to address these development and economic issues. Much funding and technical assistance has been allocated with little apparent impact on the condition of rural areas and rural people.